The Effect of Greenwashing on Switching Intention: The Mediating Roles of Green Consumer Confusion and Perceived Consumer Skepticism, and the Moderating Role of Green Perceived Risk (A Case Study on PlantBottle Coca-Cola Consumers among Indonesian Citizens) - Meliyana Rizki Prabaningrum; Suliyanto Suliyanto; Refius Pradipta (Dinasti Publisher, 2025)
This study investigates the influence of greenwashing on switching intention by examining the roles of green perceived risk, green consumer confusion, and perceived consumer skepticism. A quantitative approach was employed, using surveys distributed to Indonesian consumers who had purchased PlantBottle Coca-Cola products in eight different countries. A total of 120 valid responses were collected and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software. The results indicate that greenwashing does not have a direct effect on switching intention. Furthermore, green consumer confusion does not mediate this relationship. However, perceived consumer skepticism significantly mediates the relationship between greenwashing and switching intention. Additionally, green perceived risk does not moderate the effect of greenwashing on switching intention. These findings underscore the importance for companies to communicate environmental claims transparently and credibly. Misleading sustainability messages may foster consumer skepticism, which can ultimately undermine brand loyalty and increase switching behavior. In the context of eco-friendly branding, this study contributes to a deeper understanding of the psychological mechanisms that drive negative consumer reactions to greenwashing.